Предмет: Алгебра,
автор: zayczewars
решите систему уравнений {(y+1)(x-12)=0 {(x-y+2)/(y-2)=5
Ответы
Автор ответа:
8
(y+1)(x-12)=0
(x+y+2)/(y-2)=5
(y+1)(x-12)=0
x=y+2=5y-10
(y+1)(x-12)=0
x=6y-12
(y+1)(6y-12-12)=0
y=-1
y=4
x=6*(-1)-12
x=6*4-12
x=-18
x=12
x1=-19
y1=-1
x2=12
y2=4
(-1+1)*(-18-12)=0
-18-(-1)+2/-1-2=5
(4+1)*(12-12)=0
12-4+2/4-2=5
0=0
5=5
0=0
5=5
x1=-18
y1=-1
x2=12
y2=4
(x+y+2)/(y-2)=5
(y+1)(x-12)=0
x=y+2=5y-10
(y+1)(x-12)=0
x=6y-12
(y+1)(6y-12-12)=0
y=-1
y=4
x=6*(-1)-12
x=6*4-12
x=-18
x=12
x1=-19
y1=-1
x2=12
y2=4
(-1+1)*(-18-12)=0
-18-(-1)+2/-1-2=5
(4+1)*(12-12)=0
12-4+2/4-2=5
0=0
5=5
0=0
5=5
x1=-18
y1=-1
x2=12
y2=4
Похожие вопросы
Предмет: Право,
автор: NikitAss777
Предмет: Математика,
автор: danielyanerik25
Предмет: Физика,
автор: koko7879
Предмет: Биология,
автор: alenabazaeva194
Предмет: Математика,
автор: дашик23012005